The design of pension pay out options when the health status during retirement is uncertain - Mathias Kifmann (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper examines the optimal design of pension plans when the health status during retirement is uncertain. Assuming that the health status affects both life expectancy and the marginal utility of consumption, choice between a lump-sum payment and an annuity can be welfare-enhancing if the health status is not observable by pension plans. This result holds if the marginal utility of consumption and life expectancy are negatively correlated. On equity grounds, a lump-sum option can be justified even if the marginal utility of consumption is independent of life expectancy.
Keywords: G23; H55; D82; 330; pensions; lump-sum withdrawal; annuities; longevity; Alterssicherung; Sterblichkeit; Kapitalertrag; Portfolio-Management; Entscheidung bei Unsicherheit; Zeitpräferenz; Theorie